Is there a desired added worker effect? Evidence from involuntary job losses - Mattis Beckmannshagen; Rick Glaubitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Existing research has found little to no evidence for an added worker effect. However, studies to date have only analysed individuals' actual labor supply responses to their partners' job loss, neglecting to consider a potential mismatch between desired and actual labor supply adjustments. Using data from the German Socio-Economic Panel (SOEP), we study individuals' changes in actual and desired working hours after their partners' involuntary job loss in an event study design. Our results show that neither desired nor actual working hours change significantly. Thus, we provide first evidence that the absence of the added worker effect is in line with individuals' stated labor supply preferences and is not the result of an inability to realise desired working hours.
Keywords: J22; H55; 330; labor supply; desired working hours; added worker effect; event study